Novel effects of phytoestrogenic soy isoflavones on serum calcium and chloride in premenopausal women: A 2-year double-blind, randomized, placebo-controlled study - Lu, Lee-Jane W.; Chen, Nai-Wei; Nayeem, Fatima; Ramanujam, V-M. Sadagopa; Kuo, Yong-Fang; Brunder, Donald G.; Nagamani, Manubai; Anderson, Karl E. (Clinical nutrition (Edinburgh, Scotland), 2018)
Soy phytoestrogens are potential alternatives to postmenopausal hormone replacement therapy (HRT). Adverse effects of HRT such as myocardial infarction, stroke, and pulmonary embolism are mediated by calcium-induced signaling. To determine whether soy isoflavones affect serum calcium in healthy female subjects. In a double-blind trial, 197 premenopausal women were randomly assigned to either isoflavone (N = 99) or placebo pills (N = 98) 5 days per week for up to 2 years, plus prenatal vitamins. Isoflavone pills contained 60 mg genistein, 60 mg daidzein and 16.6 mg glycitein (expressed as aglycone equivalents). All pills contained 15 mg riboflavin as an adherence marker. Blood chemistries and urinary daidzein, genistein and riboflavin were measured multiple times during the luteal phase before and during treatment. Analysis of the adherent population (N = 83 per group), revealed significantly strong associations between urinary levels of isoflavones and serum concentrations of calcium (regression coefficients 0.082 for daidzein and 0.229 for genistein, all P < 0.01) and chloride (regression coefficient, −1.537 for genistein, P < 0.0001), mediated in part by albumin. The effects amounted to mean changes of +0.24 mg/dL for calcium and −1.45 mEq/L for chloride, with each visit for subjects excreting the most vs. the least amounts of isoflavones. These associations were not evident in the intention-to-treat analysis (N = 197) that did not assess expected variations in isoflavone levels within and between subjects from metabolism and adherence. These novel and strong effects of soy isoflavones on calcium homeostasis have important implications for long term effects of these natural substances on cardiovascular diseases.